2011
DOI: 10.3109/09687637.2011.608392
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for managing alcohol at large events in New Zealand

Abstract: This article proposes strategies that can be applied to eliminate or reduce alcohol-related problems when planning for large events at venues throughout New Zealand. It further recommends the development of an alcohol management plan specific to an event and its venue that identifies alcohol-related risks and details how the strategies proposed in this article will be implemented. Alcohol-related problems at large events including violence, anti-social behaviour and traffic-related offences are commonly report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The negative MWTP value on the ALCOH attribute revealed that sports event tourists attending KBO league games were willing to pay KR₩84 if the alcohol content would decrease by 1%. The vast majority of previous studies (e.g., Lyne & Galloway, 2011; Merlo et al, 2010) have raised a public concern that consuming beverages with a higher alcohol percentage increase the likelihood of engaging in destructive fan behaviors. Nevertheless, our respondents exhibited their desires for sober attendance experience while drinking beer with lower alcohol.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The negative MWTP value on the ALCOH attribute revealed that sports event tourists attending KBO league games were willing to pay KR₩84 if the alcohol content would decrease by 1%. The vast majority of previous studies (e.g., Lyne & Galloway, 2011; Merlo et al, 2010) have raised a public concern that consuming beverages with a higher alcohol percentage increase the likelihood of engaging in destructive fan behaviors. Nevertheless, our respondents exhibited their desires for sober attendance experience while drinking beer with lower alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…Since sports event tourists often view alcohol, particularly beer, as a symbol of celebration, alcoholic beverages are available at stadium concession booths although some countries still prohibit in-stadium alcohol consumption due to their religious and cultural backgrounds (Lyne & Galloway, 2011). From the managerial perspectives, selling alcohol is an important revenue source for sports clubs (Mitchell & Montgomery, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation